2023
DOI: 10.2141/jpsa.2023011
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of the Probiotic <i>Clostridium butyricum</i> on Gut Microbes, Intestinal Health, and Growth Performance of Chickens

Abstract: Clostridium butyricum is an important probiotic for chickens and exerts various biological activities, including altering the composition of the intestinal microbiota, competing with other microorganisms for nutrients, improving the integrity of the intestinal mucosal system, changing the intestinal barrier, and improving overall host health. Intestinal microbes also play vital roles in maintaining the intestinal barrier, regulating intestinal health, and promoting chicken growth. During chicken pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…Numerous in vivo and in vitro studies have confirmed that probiotics can improve the balance of microbes in the intestinal environment, enhance immune function, and benefit intestinal morphology [16][17][18][19][20][21][22]. In all of these studies, Clostridium butyricum (C. butyricum) has been identified as an effective probiotic that promotes animal growth and maintains intestinal barrier function [20,[23][24][25][26][27][28][29]. C. butyricum, also known as Clostridium tyrosine, is a Gram-positive obligate anaerobic bacillus first isolated from pig intestines in 1880 by Prazmowski.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vivo and in vitro studies have confirmed that probiotics can improve the balance of microbes in the intestinal environment, enhance immune function, and benefit intestinal morphology [16][17][18][19][20][21][22]. In all of these studies, Clostridium butyricum (C. butyricum) has been identified as an effective probiotic that promotes animal growth and maintains intestinal barrier function [20,[23][24][25][26][27][28][29]. C. butyricum, also known as Clostridium tyrosine, is a Gram-positive obligate anaerobic bacillus first isolated from pig intestines in 1880 by Prazmowski.…”
Section: Introductionmentioning
confidence: 99%